THE EFFECT OF BRAND EQUITY AND PERCEIVED PRICE OF GOJEK TO CUSTOMER SATISFACTIONTHE EFFECT OF BRAND EQUITY AND PERCEIVED PRICE OF GOJEK TO CUSTOMER SATISFACTION - Mourine Oroh; Maryam Mangantar; Regina T. Saerang (Universitas Sam Ratulangi, 2023)
Currently, there are many digital products that are developing very rapidly besides computers, namely smartphones and the Internet, not only in the field of communication but also in the field of public transportation, which with the help of current technology has led to new innovations, namely an application for online ride hailing calls via smartphones such as Gojek and other brands. This study examines the effect of brand equity and perceived price of the Gojek brand on customer satisfaction. This study used a quantitative research method with 100 samples using a questionnaire data collection technique, then tested using multiple linear multiple techniques. The results of the study stated that brand equity and perceived price of the Gojek brand have a positive and significant effect on customer satisfaction. Gojek must continue to maintain and improve its good quality and performance in order to maintain consumer interest in using the Gojek brand rather than other brands. Keyword: brand equity, perceived price, customer satisfaction